THE EFFECT OF THE LOCK AND KEY STRATEGY ON THE CREATIVE THINKING SKILLS OF MIDDLE SCHOOL FEMALE STUDENTS IN MATHEMATICS - Shaimaa Abdul Hamza Zaboon (Scholars Digest Publishing, 2024)
The current study aimed to identify (the impact of the lock and key strategy on the creative thinking skills of middle school students in mathematics), the researcher followed the experimental approach, on a sample of (79) female students from the first intermediate students in (Sumer High School for Girls) in the General Directorate of Education of Baghdad / Rusafa II for the academic year 2023/2024 in the second semester, distributed over two groups (experimental and control), by (40) students in the experimental group, and (39) students in the control group, and the researcher prepared a test For creative thinking skills consists of (20) objective paragraphs of the type (multiple choice) on four main skills are (fluency, flexibility, originality, expansion and elaboration) for each skill (5) paragraphs, and the results of the study found a statistically significant difference between the average scores of the experimental group students who studied mathematics using the lock and key strategy and the control group who studied the same material using the usual method in testing creative thinking skills, and for the benefit of the experimental group, In light of this result, the researcher made some recommendations and suggestions.
Keywords: Lock and key strategy - Creative thinking skills - Middle school students – Mathematics